Hygric deformation of hardened cement paste with limestone-rich cements under cyclic ad- and desorption. (18th July 2022) - Herget, Christian; Rezvani, Moien; Louisa Müller, Anna; Proske, Tilo
Highlights: Measurements of the shrinkage behavior of hardened cement paste containing high volume limestone powder. Measurements of reversible and irreversible shrinkage of hcp. Porosity and specific surface area increases by increasing limestone powder content. Increasing limestone powder content increases total shrinkage but decreases the ratio of reversible and total shrinkage. Shrinkage of hcp containing limestone powder is mainly affected by the impurities, expressed by the methylene blue value, in the limestone. Abstract: Substitution of Portland cement clinker by limestone powder can significantly reduce the environmental impact of cement and concrete. At the same time, shrinkage will decrease. Within this study, the shrinkage behavior was analyzed on cement pastes made with limestone-rich cements during cyclic ad- and desorption. With an increasing limestone volume, a higher ratio of irreversible shrinkage was observed. A high influence of the clay content of the limestone on the ad- and desorption behavior of limestone-rich cements was revealed, notwithstanding of the minor influence on the pore structure. Water vapor sorption isotherm measurements showed, that the pores coarsened by first drying and cannot be refilled totally later at 95 %RH. Mercury intrusion porosimetry and helium pycnometry indicated a higher proportion of meso- and macropores by increasing limestone volume at constant w/c-ratio. Finally, an analytical prediction model is presented to predict the reversible shrinkage strain of cement pastes made with limestone-rich cements.